Can China Promote Electronic Commerce through Law Reform – Some Preliminary Case Study Evidence - Winn, Jane K.; Yuping, Song (Columbia Journal of Asian Law, 2007)
The government of the People’s Republic of China (P.R.C.) has announced its intention to make China a global leader in innovation by 2020. Many Chinese business leaders share this goal. The primary focus of this national strategy is to transform China into an exporter of high-technology products based on Chinese designs rather than merely a low cost, high volume manufacturer of products based on technology developed in other countries. This paper will examine the implications for this strategy with regard to the use of computerized management information systems by Chinese businesses, and its relationship to recent law reform efforts intended to promote greater use of electronic commerce among Chinese businesses. This paper considers three case studies of recent reforms of P.R.C. commercial law in light of their contributions to this strategy, and finds that the results so far are quite mixed. The first case study looks at a domestic standard for accounting software issued in 1989 that successfully removed obstacles to the greater use of computerized accounting systems by local businesses and promoted the growth of the domestic accounting software industry. The second and third case studies involve P.R.C. legislation based on model laws developed by United Nations Commission on International Trade Law (UNCITRAL) developed to assist legislators in trading nations to harmonize their national commercial laws in order to eliminate barriers to international trade. The second case study looks at the inclusion of general electronic commerce enabling legislation in the 1999 Contract Law which in theory removed impediments to the use of electronic commerce by Chinese businesses but in reality appears to be too abstract and general to provide much certainty to parties wishing to form contracts using electronic media. The third case study looks at the 2004 Electronic Signature Law which promotes the use of a specific type of technology for authentication. While it is too soon to know whether this law will achieve its intended objectives in China, evidence from other countries with similar laws suggests that it may not.